Teacher ratings and standardised test scores: how good for predicting achievement in students with learning support placement? - Maunganidze, Levison; Ruhode, Nancy; Shoniwa, Loice; Nyanhongo, Solomon; Kasayira, Joseph M.; Sodi, Tholene (Routledge, 2021)
The study analysed the relationships between teacher ratings and standardised test scores in Reading and Mathematics for students receiving learning support for learning difficulties (n = 60, mean age= 16.3). Teacher ratings were found to significantly predict pupils' performance in Reading. Students with extended learning support had significantly higher teacher attainment ratings in both Reading and Mathematics. Teacher judgment ratings combined with standardized test scores were reliable for assessing instructional effectiveness. Standardised tests were more reliable than teacher ratings in assessing academic attainment.